Metal-free synthesis of N-sulfonylformamidines via skeletal reconstruction of sulfonyl oximonitriles. Issue 3 (17th December 2021) - Li, Feng; Wu, Ziyan; Wang, Jingjing; Zhang, Siyuan; Yu, Jiaxin; Yuan, Zhen; Liu, Jingya; Shen, Renzeng; Zhou, Yao; Liu, Lantao
Abstract : We firstly develop an unprecedented domino reaction of sulfonyl oximonitriles with secondary amines to streamline synthesis of  N -sulfonylformamidines in decent to high yields under mild reaction conditions. Abstract : We developed for the first time an unprecedented domino reaction of sulfonyl oximonitriles with secondary amines to streamline the synthesis of N -sulfonylformamidines in decent to high yields under mild reaction conditions. In addition, scale-up experiments and late-stage functionalization of drugs were also performed. Preliminary studies indicate that the loss of a cyano-/benzyloxy-group and a sulfonyl migration process are involved in this reaction.